In Between Familiar-Unfamiliar: Research Travel as Arts-Based Research - Morimoto, Ken; Mosavarzadeh, Marzieh (Journal of the Canadian Association for Curriculum Studies, 2020)
Artists, researchers and teachers often find their work positioned in-between the familiar and the unfamiliar. The arts linger in-between such familiar-unfamiliar events, objects and places, unfolding new understandings and potentialities by making the familiar strange and the unknown familiar. Through a collaborative arts-based educational research project conducted in Japan, we address the following question: How can artistic practices lend to pedagogical possibilities when we attend to new things in familiar ways, and when we situate familiar things in new ways? Through a combination of a/r/tography and walking method, we engage in a series of walks, conversations and creative practices that explore layers of relationality through research travel. Walking as an arts-based research practice emphasizes the physicality of our nature as an embodied being grounded in movement; “walking is not just what a body does; it is what a body is” (Ingold & Vergunst, 2008, p. 1). Working together from different perspectives troubles a binary understanding of the insider-outsider relationship, focusing instead on the “-“ as a site of a hyphenated positionality. The walking sessions form a relational correspondence with each other that reveal rhythms of our walks, relationships and experiences while we attune ourselves to ways of lingering in-between familiar and unfamiliar places. Through the embodied and metaphorical walking in-between the familiar-unfamiliar, we consider the pedagogical implications of research travel as site of collaborative arts-based inquiry and what further questions they may raise.